Drifting Without an Anchor: How Pitch Accents Withstand Vowel Loss. (March 2015) - Baltazani, Mary; Kainada, Evia
We offer an analysis of the influence exerted by segmental rules on the suprasegmental structure in the dialect of Ipiros Greek (IG). In particular we investigated how vowel deletion (VD) affects the phonetic realization of the L*+H pitch accent. Our data empirically establish that the H tone aligns much earlier when VD applies than when it does not. Furthermore, we show that there is a phonological contrast between the nuclear L+H* and the prenuclear L*+H which hinges on early versus late H alignment respectively. We demonstrate that the contrast between the L*+H and the L+H* pitch accents is not compromised by the earlier alignment caused by VD. In other words, intonational contrasts are not endangered by fine phonetic alignment variability within the same category.